Jus Pegagan: Inovasi Pelatihan Kader Untuk Meningkatkan Pemanfaatan Tanaman Herbal - Muryani, Ni Made Sri; Daryaswanti, Putu Intan; Putra, I Gede Yudiana; Widayanata, Komang Agus Jerry; Artawan, I Kadek; Pendet, Ni Made Diah Pusparini (Sekolah Tinggi Ilmu Kesehatan KESDAM IX/Udayana, 2023)
Background: Family medicinal plants represent a local resource that communities can utilize to support health promotion and disease prevention efforts. Ketewel Village in Gianyar Regency has cultivated these plants; however, their utilization remains suboptimal due to the community's limited knowledge and skills regarding herbal plant processing. Centella asiatica is an herbal plant rich in bioactive compounds with the potential to be developed into easily consumable processed products. One initiative to enhance the utilization of centella asiatica involves training community health volunteers in the production of centella asiatica juice. Method: This community service activity was conducted in Ketewel Village, Sukawati District, Gianyar Regency, involving five health volunteers. The implementation method included providing education on the benefits of centella asiatica, demonstrating how to make centella asiatica juice, and hands-on practice by the volunteers. Evaluation was carried out by observing the volunteers' skills in the centella asiatica juice preparation process before and after the training. Results: The results of the activity indicate an improvement in the cadres' skills in processing centella asiatica into herbal juice. Prior to the training, none of the cadres were able to process centella asiatica; however, following the training, all cadres (100%) were able to independently produce centella asiatica juice according to the prescribed steps. The cadres also gained an understanding of the benefits of centella asiatica, processing techniques, and hygiene principles involved in herbal product preparation. Conclusion: Training on making centella asiatica juice is effective in enhancing the skills of community health volunteers in utilizing local herbal plants. This activity can serve as a community empowerment strategy to optimize the use of medicinal plants in home gardens and support health promotion and prevention efforts based on local resources.